Efficient filter flow for space-variant multiframe blind deconvolution - Hirsch, M; Sra, S; Scholkopf, B; Harmeling, S (2010 IEEE Computer Society Conference on Computer Vision and Pattern Recognition, 2010)
Ultimately being motivated by facilitating space-variant blind deconvolution, we present a class of linear transformations, that are expressive enough for space-variant filters, but at the same time especially designed for efficient matrix-vector-multiplications. Successful results on astronomical imaging through atmospheric turbulences and on noisy magnetic resonance images of constantly moving objects demonstrate the practical significance of our approach.